Influence of the Local Economy by Implementing Marketing Mix on Farmers - Rahman, Moh Abd (STAI Nurul Islam Mojokerto, 2025)
This research explores the influence of the marketing mix and consumer preferences on the local economy, focusing on durian farmers in Guyangan Village. Data from 23 respondents, including consumers and farmers, was analyzed using quantitative methods. The results show that marketing mix factors such as price, distribution, promotion, and product have a significant effect on consumer preferences (p less than 0.05). As many as 78% of respondents showed a positive preference for local durian. Regression analysis found that consumers' positive preferences for local durian products were significant in local economic growth (p less than 0.01). These findings highlight the importance of appropriate marketing strategies and understanding consumer preferences to support the local economy, especially in durian farming in Guyangan Village.